Maxillary Distraction Osteogenesis Versus Conventional Orthognathic Surgery in Cleft Lip and Palate Patients: Systematic Review - Eid, Alia; Ahmed, Ranad; Yehia, Mahmoud; Abdelfattah, Salah (The Journal of craniofacial surgery, 2025)
Cleft lip and palate (CLP) is a common congenital condition that often requires multiple surgeries to correct. However, these surgical procedures can lead to complications like midface hypoplasia, speech difficulties, and dental malocclusion. CLP individuals need orthognathic surgeries to correct these problems either with conventional Le Fort I (CO) or maxillary distraction osteogenesis (DO). The search of the articles was through 3 main electronic databases PubMed, Science Direct, Scopus. Clinical trials, prospectives, retrospective, and case series were included. A total of 30 articles were analyzed according to the type of orthognathic surgery and the outcomes relapse, soft tissue, velepharyngeal insufficiency (VPI), Speech, and morbidities. The results showed that there was no difference between CO and DO in terms of relapse rate, soft tissue changes, speech, and morbidities. However, DO showed less change on the veloparyngeal gap than CO.